Breathable waveguides for combined light and CO2 delivery to microalgae. (June 2016) - Pierobon, Scott C.; Riordon, Jason; Nguyen, Brian; Sinton, David
Graphical abstract: Highlights: A permeable waveguide is used for combined light and CO2 delivery to microalgae. CO2 delivery using permeation led to double the growth as compared to a control. Cellulose acetate butyrate was a suitable breathable waveguide material. Abstract: Suboptimal light and chemical distribution (CO2, O2 ) in photobioreactors hinder phototrophic microalgal productivity and prevent economically scalable production of biofuels and bioproducts. Current strategies that improve illumination in reactors negatively impact chemical distribution, and vice versa. In this work, an integrated illumination and aeration approach is demonstrated using a gas-permeable planar waveguide that enables combined light and chemical distribution. An optically transparent cellulose acetate butyrate (CAB) slab is used to supply both light and CO2 at various source concentrations to cyanobacteria. The breathable waveguide architecture is capable of cultivating microalgae with over double the growth as achieved with impermeable waveguides.